Opposition ved Kaj Mogensens forsvar for disputatsen: Livet - det dejligste eventyr. H.C. Andersens teologi - Nielsen, Kirsten (Dansk Teologisk Tidsskrift, 2018)
This article is a short version of my opposition at Kaj Mogensen’s public defense of his doctoral dissertation, Life – the most wonderful story. The theology of H.C. Andersen. While most scholars have concentrated their studies on only one genre, Kaj Mogensen analyzes Andersen’s most important novels The two Baronesses, To be or not to be and Lykke-Peer, the long drama “Ahasverus” and various poems and hymns as well as a few of his fairy tales. Mogensen reads the texts in their cultural context and argues that Andersen’s theology is a challenge to modern theology. At the public defense, I challenged Mogensen to discuss his understanding of Andersen’s use of intertexts and Mogensen’s own criteria for including intertexts (often biblical intertexts) in his interpretations.